2020
DOI: 10.1088/1475-7516/2020/02/028
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational wave anisotropies from primordial black holes

Abstract: An observable stochastic background of gravitational waves is generated whenever primordial black holes are created in the early universe thanks to a small-scale enhancement of the curvature perturbation. We calculate the anisotropies and non-Gaussianity of such stochastic gravitational waves background which receive two contributions, the first at formation time and the second due to propagation effects. We conclude that a sizeable magnitude of anisotropy and non-Gaussianity in the gravitational waves would s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 75 publications
0
92
0
Order By: Relevance
“…Such an enhancement of the curvature perturbations are often considered in the context of the primordial black hole (PBH) [23][24][25] (see also Refs. [7,[26][27][28][29][30][31]). PBHs have recently been studied by many authors mainly because they can be a dark matter (DM) candidate and may explain the binary black hole merger events observed by LIGO/Virgo [32].…”
Section: Introductionmentioning
confidence: 99%
“…Such an enhancement of the curvature perturbations are often considered in the context of the primordial black hole (PBH) [23][24][25] (see also Refs. [7,[26][27][28][29][30][31]). PBHs have recently been studied by many authors mainly because they can be a dark matter (DM) candidate and may explain the binary black hole merger events observed by LIGO/Virgo [32].…”
Section: Introductionmentioning
confidence: 99%
“…In close analogy to the analysis of CMB photons, we can now ♦4 See Refs. [7][8][9][10][11][12][13] for related analysis of the anisotropies of the SGWB. ♦5 For inflationary GWs, we take "source time" labeled by "s" to be when the relevant GWs are well inside the horizon.…”
Section: Intuitive Explanation Of the Resultsmentioning
confidence: 99%
“…The result for the SW term in ∆lnf (1) is in particular consistent with the results derived in Refs. [7,12].…”
Section: A2 Step 1: Gw Spectrum At the Sourcing Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, the GW detectors would detect GWs from different directions, resulting in angular anisotropies of the SIGW signal. This was studied in [141]. In the absence of primordial non-Gaussianities, the authors found that the anisotropies are negligible by today due to the propagation effects.…”
Section: Scalar-induced Gravitational Wavesmentioning
confidence: 99%